Organizational Governance Capacity and Organizational Resilience in Hospitals: A Cross-sectional Study - Afşar, Leyla; Yazıcı, Selim (Makara Journal of Health Research, 2026)
Background: This study aims to examine the relationship between organizational governance capacity (OGC) and organizational resilience (OR) in hospitals, with a focus on cross-institutional differences. Methods: A cross-sectional study was conducted among 1,143 employees from six hospital types in Istanbul, including university, Ministry of Health (state, training and research, and city), and private hospitals. Validated scales were used to measure OGC and OR. Data were analyzed using descriptive statistics, nonparametric tests, and structural equation modeling (SEM) to assess the relationships between these dimensions. Results: Private hospitals demonstrated the highest levels of both OGC and OR (70%), followed by Ministry of Health hospitals (60%, medium-high), and university hospitals (40%, medium-low). SEM revealed positive and significant relationships between all OGC and OR dimensions except between responsibility capacity and planning. The strongest association was observed between self-organization and adaptive capacity (β = 0.654, p < 0.001). Conclusions: Strengthening governance—particularly self-organizing and adaptive capacities—can enhance hospitals’ resilience and crisis responses. Future longitudinal studies are recommended to explore causal mechanisms between governance and resilience.